Nature-Related Financial Risks in Brazil - Calice, Pietro; Diaz Kalan, Federico; Miguel, Faruk (World Bank, Washington, DC, 2021)
Biodiversity loss and associated economic costs are increasingly recognized as a source of financial risks. This paper explores how and to what extent Brazilian banks are exposed to the loss of biodiversity through their lending to non-financial corporates. The results suggest that such exposures are material. Forty-six percent of Brazilian banks’ non-financial corporate loan portfolio is concentrated in sectors highly or very highly dependent on one or more ecosystem services. Output losses associated with the collapse in ecosystem services could translate into a cumulative long-term increase in corporate nonperforming loans of 9 percentage points. Moreover, 15 percent of Brazilian banks’ corporate loan portfolio is to firms potentially operating in protected areas, which could increase to 25 percent should conservation gaps close, and 38 percent should all priority areas become protected. Finally, 7 percent of corporate loans are to firms for which environmental controversies have been recorded. While preliminary, the results have important policy implications for both Brazilian banks and Banco Central do Brasil.